Information, Asset Prices, and the Volume of Trade. - Huffman, Gregory W (Journal of Finance, 1992)
A dynamic equilibrium model is constructed in which agents with access to different information sets participate in the capital market. Agents must use the equilibrium price of capital to make optimal forecasts of the return to holding capital. Examples show that the volume of trade, as well as the price of capital, can be highly correlated with a measure of the information content of prices. The measure of information is the difference between the unconditional entropy of the dividend and the entropy of the dividend conditional on observing the price of capital.